Polymer/montmorillonite nanocomposites with improved thermal properties: Part I. Factors influencing thermal stability and mechanisms of thermal stability improvement. - Leszczynska, Agneska; Njuguna, James A. K.; Pielichowski, Krzysztof; Banerjee, J. R. (Elsevier Science B.V., Amsterdam., 2007)
The results of recent research indicate that the introduction of layered silicate – montmorillonite – into polymer matrix results in increase of thermal stability of a number of polymer nanocomposites. Due to characteristic structure of layers in polymer matrix and nanoscopic dimensions of filler particles, several effects have been observed that can explain the changes in thermal properties. The level of surface activity may be directly influenced by the mechanical interfacial adhesion or thermal stability of organic compound used to modify montmorillonite. Thus, increasing the thermal stability of montmorillonite and resultant nanocomposites is one of the key points in the successful technical application of polymer–clay nanocomposites on the industrial scale. Basing on most recent research, this work presents a detailed examination of factors influencing thermal stability, including the role of chemical constitution of organic modifier, composition and structure of nanocomposites, and mechanisms of improvement of thermal stability in polymer/ montmorillonite nanocompo
Keywords: Polymer nanocomposites; Montmorillonite; Thermal stability; Degradation